Strategies of Language Learning among Tourism College Students in Bali - Dika Pranadwipa Koeswiryono; I Wayan Suadnyana; Francisca Titing Koerniawaty (Acitya: Journal of Teaching and Education, 2023)
This study is conducted to discover the learning strategies used by more successful and less successful language learners at a tourism college in Bali. This mix-method research combined quantitative data from the questionnaire with qualitative narration obtained from a semi-structured interview. Thirty students were asked to fill in the Strategy Inventory of Language Learning (Oxford 1990). The next step was the interview, whose questions were based on their SILL results; it scrutinized the explanation of the low or high rate that they had given. The result showed that metacognitive strategies were the most prevalent among students in both groups. On the other side, the least used strategies for more successful learners were those of memory, whereas the less successful ones most rarely used compensation strategies. The interview revealed that the more successful participants improve their English by watching movies or reading books. The other strategies were taking notes and using new words in conversation, as well as making guesses on new words, and writing in a diary. Language learners could refer to those strategies to accelerate their learning progress. Teachers should also be aware of the diverse strategies and inform the students about the other alternative strategies that might suit their weaknesses, strengths, or learning style. It is also very helpful to provide an environment where students could explore different strategies, either by making access to native speakers available or by assigning diary writing and portfolio.